A Dynamics-Based Adaptive String Stable Controller for Connected Heavy Road Vehicle Platoon Safety - K. B. Devika; G. Rohith; Venkata Ramani Shreya Yellapantula; Shankar C. Subramanian (IEEE Access, 2020)
This article presents a string stable controller for the autonomous operation of a platoon of Heavy Commercial Road Vehicles (HCRVs) in a connected environment. This study considers factors such as brake/powertrain actuator dynamics, resistive forces, tyre model and wheel dynamics, which are crucial during on-road operation of HCRVs. A nonlinear vehicle dynamic model encompassing all these factors has been considered. The dependency between aerodynamic drag and inter-vehicular distance in the platoon has also been taken into account. The aforementioned factors motivated the use of Sliding Mode Control (SMC), which is a nonlinear and robust control technique. A lower level Proportional Integral Derivative (PID) controller has been successfully integrated with SMC to compensate for pneumatic brake and powertrain system delay. The designed controller was evaluated for string stable platoon operation by considering various road conditions, load conditions and operating speeds. It was observed that the string stable controller performance is highly dependent on the operating conditions. To ensure string stable operation for different operating scenarios, an adaptive time-headway based enhancement has also been integrated in the controller design. The efficacy of the proposed adaptive time-headway policy over the existing constant time-headway policy has been methodically analysed and a performance comparison between them has also been presented. The aspect of communication delay during connected vehicular operation has also been studied and the maximum tolerable communication delay magnitude for maintaining string stable operation has also been presented.